Number and Activity of Microorganisms in Organic and Conventional Soil in Subak Blongyang Tabanan, Bali, Indonesia - Avianto, Rio Jonathan; Kartini, Ni Luh; Soniari, Ni Nengah (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2023)
Microorganisms are most broadly used as an indicator of soil fertility and quality. Organic farming is an agricultural technique that does not use synthetic pesticides or fertilizers, believed to be a solution to the negative impacts of conventional farming systems. This study aimed to compare soil microbial numbers and activities in organic and conventional paddy fields and determine their influencing factors in Subak Blongyang, Tabanan, Indonesia. The research methods comprised literature study, field survey, soil sampling, and soil analysis in the laboratory, with soil respiration as a measure of microbial activity. Afterward, the data derived were tabulated and analyzed descriptively. Results show that the total microorganisms (19.16x106 cfu/g) and soil respiration (8.58 mgC-CO2/kg/day) in organic paddy fields were higher than in samples collected from conventional paddy fields (2.46 x106 cfu/g; 5.82 mgC-CO2/kg/day). Similarly, the laboratory tests of various supporting variables indicate that soils in the former were always more favorable for microbial growth and activities than the latter, as seen from total-N, organic-C, organic matter, C/N ratio, and soil pH.